Ranger's apprentice - Flanagan, John (John Anthony) (New York Puffin Books, an imprint of Penguin Group (USA), 2013)
In 1896, an archaeological dig unearths an ancient trunk containing manuscripts that confirm the existence of Araluen Rangers Will and Halt and tell of their first meeting and some of their previously unknown exploits
1
Keywords: Apprentices -- Fiction; War -- Fiction; Fantasy fiction